Спектрометрический стенд для измерения сцинтилляционных характеристик сцинтилляторов и детекторов на основе системы «сцинтиллятор – pin фотодиод» - Кудин, А. М.; Бороденко, Ю. А.; Белогуб, В. В.; Диденко, А. В. (НТУ "ХПИ", 2014)
Представлены результаты разработки и изготовления спектрометрического стенда для тестирования сцинтилляционных сборок, выполненных на основе системы «сцинтиллятор CsI:Tl – PIN фотодиод». Показано, что изготовленные сборки и разработанный спектрометр удовлетворяют жестким требованиям для приборов, предназначенных для исследования солнечной радиации в космических условиях.

Scintillation spectrometer for testing so called photodiode detectors has been developed. A pecu-liarity of this device is a low background of noise (500 electrons at a 10 kHz band). Spectrometric char-acteristics of two types of detection assemblies for space research on a base of CsI:Tl crystal and PIN photodiode were measured. It has been shown that developed assemblies and scintillation spectrometer satisfy to strong requirements for devices intended for study a solar radiation in space.
Spectrometric stand for measuring scintillation characteristics scintillators and detectors on the basis of the «scintillator - pin photodiode»
Keywords: космические исследования; сцинтилляционные сборки; PIN фотодиод; спектрометрия; энергетическое разрешение; гамма -изотопы; scintillator; PIN photodiode; detector; spectrometry; energy resolution